Urgensi Undang-Undang ITE di Era Globalisasi - Nur Qalbi Putri Ramadhani Ahmad (Jurnal Litigasi Amsir, 2022)
The Electronic Information and Transaction Law (UU ITE) which the government has ratified along with the rapid development of information technology, aims to maintain and maintain polite behavior in cyberspace. However, Indonesian people feel that the existence of the ITE Law hinders freedom of expression and issuing opinions. Moreover, the ITE Law has benefits, namely the state apparatus to silence people who criticize the state. In this journal, the author explains the various effects of the ITE Law on people's lives and the impact it has caused. In conclusion, the principles of the ITE Law have good intentions for use to protect Indonesian people on social media. The greater the development of information technology in cyberspace and social media, the bigger the risks that may be faced. The community also wants the government to immediately remove articles that are prone to be misused for freedom of expression and can create democracy for both the people and the government.